Sclerosing Peritonitis: A Rare but Fatal Complication of Peritoneal Inflammation - Monika Merkle; Markus Wörnle (Hindawi Limited, 2012)
Sclerosing peritonitis is a rare form of peritoneal inflammation with an often fatal outcome. The major risk factor of sclerosing peritonitis is peritoneal dialysis treatment but it can also occur following renal or liver transplantation or be associated with certain drug treatment. This article gives an overview of reasons and treatment options for sclerosing peritonitis and shows a summery of current literature about sclerosing peritonitis.